2019
DOI: 10.1002/ange.201900046
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Heterostructures of Covalent Triazine Frameworks for Enhanced Photocatalytic Hydrogen Production

Abstract: Conjugated polymers have emerged as promising candidates for photocatalytic H2 production owing to their structural designability and functional diversity. However, the fast recombination of photoexcited electrons and holes limits their H2 production rates. We have now designed molecular heterostructures of covalent triazine frameworks to facilitate charge‐carrier separation and promote photocatalytic H2 production. Benzothiadiazole and thiophene moieties were selectively incorporated into the covalent triazin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 45 publications
3
52
0
Order By: Relevance
“…Hydrogen production via photocatalytic water splitting is known to be one of the most prospective and effective methods to battle the current global energy and environmental crisis. [ 1–8 ] However, to date, the best performing photocatalysts still suffer from relatively low solar‐to‐hydrogen conversion, to levels that lie far below the demand for practical applications. [ 6,8–11 ] The low efficiency of photocatalytic water splitting is attributed to three main reasons: i) the low utilization of sunlight, ii) the poor efficiency of separation and transfer of photogenerated carriers, and iii) sluggish kinetics of the hydrogen evolution reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen production via photocatalytic water splitting is known to be one of the most prospective and effective methods to battle the current global energy and environmental crisis. [ 1–8 ] However, to date, the best performing photocatalysts still suffer from relatively low solar‐to‐hydrogen conversion, to levels that lie far below the demand for practical applications. [ 6,8–11 ] The low efficiency of photocatalytic water splitting is attributed to three main reasons: i) the low utilization of sunlight, ii) the poor efficiency of separation and transfer of photogenerated carriers, and iii) sluggish kinetics of the hydrogen evolution reaction.…”
Section: Introductionmentioning
confidence: 99%
“…So far, a favorable library of morphological structures has been devised in semiconductor photocatalysts, containing 0D quantum dots, [ 22,23 ] 1D nanowires/nanorods, [ 8,24,25 ] 2D nanosheets, [ 1,12,13 ] 3D hollow nanostructures, [ 21,26 ] and heterostructures. [ 5,6,17 ] Among them, precisely designed hollow multishell structures possess attractive characteristics for photocatalysis, including efficient light harvesting, improved charge transfer, and high specific surface area. [ 17,21,27–32 ] Single/multishell hollow spheres, [ 18,33,34 ] hollow cubes, [ 35–37 ] egg yolk shells, [ 27,36,38 ] and other shaped hollow spheres have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Converting solar energy into storable chemical fuels via photocatalytic water splitting is a potentially viable route toward producing clean and sustainable energy in the future . In particular, photocatalytic overall water splitting, which can decompose pure H 2 O into stoichiometric amounts of H 2 and O 2 without using any sacrificial agents, is fundamentally important but still remains challenging . Compared to inorganic semiconductors, metal‐free polymers represent an emerging class of photocatalysts for photocatalytic overall water splitting .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that the p-stacked structure of COFs provides them with defined pathways for charge carrier transport [26][27][28]. This, in combination with the large surface area, adjustable porosity and tailorable chemistry, has enabled COFs to show a variety of potential applications.…”
Section: Introductionmentioning
confidence: 99%